A Case Presentation of Gastrointestinal Stromal Tumor of Duodenum (Journal of Renal and Hepatic Disorders, 2021)
A gastrointestinal stromal tumor (GIST) is the most common mesenchymal tumor of the gastrointestinal tract. It is caused by the mutation in KIT and PDGFRα genes. It constitutes
Keywords: cancer intervention; duodenum; tumor; surgery